Therapeutic D2/3 receptor occupancies and response with low amisulpride blood concentrations in very late‐onset schizophrenia‐like psychosis (VLOSLP). (23rd June 2017) - Reeves, Suzanne; Eggleston, Kate; Cort, Elizabeth; McLachlan, Emma; Brownings, Stuart; Nair, Akshay; Greaves, Suki; Smith, Alan; Dunn, Joel; Marsden, Paul; Kessler, Robert; Taylor, David; et al.
Abstract : Objective: Antipsychotic drug sensitivity in very late‐onset schizophrenia‐like psychosis (VLOSLP) is well documented, but poorly understood. This study aimed to investigate blood drug concentration, D2/3 receptor occupancy and outcome in VLOSLP during open amisulpride prescribing, and compare this with Alzheimer's disease (AD). Methods: Blood drug concentration, prolactin, symptoms and extrapyramidal side‐effects (EPS) were serially assessed during dose titration. [ 18 F]fallypride imaging was used to quantify D2/3 receptor occupancy. Average steady‐state amisulpride concentration (Caverage, ng/ml) was estimated by incorporating pharmacokinetic (PK) data into an existing population PK model (25 AD participants, 20 healthy older people). Results: Eight patients (target 20) were recruited (six women; 76 + − 6 years; six treatment compliant; five serially sampled; three with paired imaging data). Mean + − SD symptom reduction was 74 ± 12% (50–100 mg/day; 92.5 + −39.4 ng/ml). Mild EPS emerged at 96 ng/ml ( in AD, severe EPS, 50 mg/day, 60 ng/ml) . In three participants, imaged during optimal treatment (50 mg/day; 41–70 ng/ml), caudate occupancy was 44–59% ( 58–74% in AD across a comparable Caverage) . Conclusions: Despite the small sample size, our findings are highly relevant as they suggest that, as in AD, 50 mg/day amisulpride is associated with >40% occupancy and clinically relevant responses in VLOSLP. It was not possible to fully characterise concentration–occupancy relationships in VLOSLP, and it is thus unclear whether the greater susceptibility of those with AD to emergent EPS was accounted for by increased central drug access. Further investigation of age‐ and diagnosis‐specific threshold sensitivities is warranted, to guide amisulpride prescribing in older people, and therapeutic drug monitoring studies offer a potentially informative future approach. Copyright © 2017 John Wiley & Sons, Ltd.